Property Improvement of Fibroin from Silk Waste by Polymer Blending for Use as Food Packaging Materials - ภูษิตา คู่ชัยภูมิ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
Utilization of biopolymers from renewable sources in developing biomaterials with eco-friendly properties have found some limitations such as their poor mechanical properties, high water solubility, and low transparencies. In this study, some biopolymers, e.g., silk fibroin (SF) and rice starch (RS) were used as starting materials together with poly(vinyl alcohol) (PVA) as a film-former for preparing novel eco-friendly films. The film preparations were done by solution casting with two different blending sequences and the film compositions were optimized to obtain blended films with the highest biopolymer content and still have high strength and good flexibility. The optimal composition for PVA/RS/SF blended film preparation was 60:40 in the weight ratio of PVA:RS with 2 % w/v of SF. This optimal condition is determined by % transparency from UV-Visible spectroscopy (UV-Vis), images from scanning electron microscope (SEM) and film properties testing on mechanical properties, degree of swelling (DS), water solubility (WS) and also oxygen permeability. Moreover, these results indicated that all PVA/RS/SF blended films properties depended on their compositions and sequences of blending. The obtained blended film with optimal composition is transparent with good mechanical properties and low WS. The addition of SF helped increase the permeability of oxygen and also the degradability of the PVA/RS blended films. However, in order to improve the mechanical properties of the obtained PVA/RS/SF blended films, these films were modified by the addition of glycerol and sodium trimetaphosphate (STMP). After that the DS, WS and oxygen permeability of the glycerol and STMP modified blended films were determined, and their mechanical properties were also characterized and compared with the unmodified PVA/RS/SF blended film at the same composition. From the DS and WS results revealed that the addition of glycerol increased the DS but slightly decreased the WS of the PVA/RS/SF blended film, while, the addition of STMP led to the decrease in both DS and WS of the PVA/RS/SF blended film. Moreover, the SEM images of the glycerol and STMP modified blended films showed more homogeneity. The oxygen permeability results of the modified blended films are not much different. The addition of glycerol and STMP can improve the compatibility of the PVA/RS/SF blended films but does not much affect the oxygen permeability. However, the addition of glycerol in the PVA/RS/SF blended film increases the film flexibility. But, both of stress at break and elongation of the STMP modified PVA/RS/SF blended film are lower than the PVA/RS/SF blended film. In addition, the weakness of the properties of the obtained glycerol modified blended film is its water swelling and solubility. The hydrophobic PVA/RS/SF blended films at 60:40 % weight ratio of PVA/RS with 2 % w/w of SF were thus prepared by the addition of glycerol, and then removing of the unbound glycerol molecules by treating the films with ethanol aiming to increase the hydrophobicity of the films. Some properties of the glycerol modified PVA/RS/SF blended films including water contact angle, DS and WS were compared with the unmodified PVA/RS/SF blended films. Results from the contact angle measurement showed that the films modified with glycerol could be transformed to be hydrophobic after soaking in ethanol. The increase in soaking time tends to increase the hydrophobicity of the films. However, at about 60 min soaking, the water contact angles on the films were quite constant with the values of about 108.0±2.2º comparing with 65.3±2.4º of the ethanol-untreated PVA/RS/SF blended films. Furthermore, the ethanol-treated glycerol modified PVA/RS/SF blended films also show a little higher degree of swelling with constant solubility and better mechanical properties.